Sources of Warsaw smog and directions of remedying this situation in the place of its causes - Krystyna Guranowska-Gruszecka (Acta Scientiarum Polonorum. Architectura)
The aim of the article is to present the sources of smog in the capital city of Warsaw based on available research of sanitary institutions from recent years and original observations of phenomena. They led to the conclusion that in addition to chemical air pollution, the city’s urban planning has a significant impact, including buildings against green systems, public and individual transport by private cars, and the technical infrastructure used in buildings, as well as the application of management principles in investment activities on a larger scale which in Poland is overlooked. Apart from the analysis of contemporary source materials concerning smog as an unnatural phenomenon of the coexistence of chemical compounds and harmful dusts in the atmosphere, the directions of the situation are presented. Solutions from other European cities (e.g. Ghent) were cited. Therefore, comparative methods of Warsaw with model examples were used, introducing case study methods, presenting examples that successfully protected the urban environment. In the application part, the multi-directional directions of remedial actions are highlighted, as well as the need to apply management principles in the environmental protection actions of Warsaw, important for the achievement of the assumed goals, and not those applicable.